2023
DOI: 10.3389/fphys.2023.1174238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of growth trajectory on sexual maturation in layer chickens

Mohammad A. Bahry,
Charlene Hanlon,
Clara J. Ziezold
et al.

Abstract: Recent studies showed that apart from photostimulation, metabolic triggers may independently activate sexual maturation and egg production in chickens. However, the origin, mode of action, and specific target(s) of this metabolic control remain unknown. Beyond body weight (BW), we hypothesize that body composition (BC) and associated specific metabolic signals are involved. Thus, this study was conducted to determine the BW and BC thresholds triggering spontaneous sexual maturation in layer pullets under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
(100 reference statements)
2
1
0
Order By: Relevance
“…As found in the results, the higher energy level in the diet increased the body weight before sexual maturity and advanced age at first egg. These results were congruent with the recent study ( Bahry et al, 2023 ). The body weight at first egg and abdominal fat weight were also found to be negatively correlated with the age at first egg.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As found in the results, the higher energy level in the diet increased the body weight before sexual maturity and advanced age at first egg. These results were congruent with the recent study ( Bahry et al, 2023 ). The body weight at first egg and abdominal fat weight were also found to be negatively correlated with the age at first egg.…”
Section: Discussionsupporting
confidence: 93%
“…The low dietary energy levels resulted in a smaller body weight and body size during the rearing time, while no difference was observed between 3 groups at sexual maturity except for interpubic distance. The similar results that low-energy level depressed the body weight and delayed sexual maturity was also found in previous studies ( van der Klein et al, 2018 ; Bahry et al, 2023 ). Likewise, there was no significant difference in body weight at sexual maturity in chickens fed different dietary energy contents in previous study ( Hocking, 2004 ).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, Saleh et al (2020) reported that Mn is a cofactor in cholesterol synthesis which is precursor for the steroid hormone's production. Furthermore, Bahry et al (2023) found that plasma E2 have a positive correlation with bone mineral content and density. Therefore, we speculate that phytase might be prolong the lifetime of egg production through increasing the reproductive hormones and afforded sufficient minerals.…”
Section: Discussionmentioning
confidence: 96%
“…Egg-type pullets are known to have small BW difference when restricted-fed at 70% compared to ad libitum feeding by the time of photostimulation [32]. More recently, Bahry et al [13] showed that Lohmann Brown-Lite pullets fed ad libitum had greater BW when compared to target-fed or those fed 20% below the target BW. In the above study, pullets were fed conventionally [13], similarly to the present study, where the CON experiment showed larger BW differences in the ad libitumvs.…”
Section: Body Weight and Coefficient Of Variationmentioning
confidence: 99%
“…Restricted pullets have lower maintenance requirements, consuming less feed and being more efficient [11]. On the other hand, severe feed restriction during the rearing period can limit nutrient intake and decrease BW and egg production [12,13]. Additionally, restricted birds have increased lean mass deposition [14], which can further prevent birds from developing hemorrhagic liver syndrome [15], but also may decrease reproductive capacity.…”
Section: Introductionmentioning
confidence: 99%